Kinerja Pegawai Pada Bagian Pemerintahan Di Sekretariat Daerah Kabupaten Gorontalo Utara - Zees, Sri Irna Hardiyatni; Rumapea, Patar; Liando, Daud Markus (JURNAL ILMIAH SOCIETY, 2016)
The aims of this research are to examine and analyze the part of government employee performance based on the side at work motivation, the ability to work and the labor discipline on the part of Government Employees In Northern Gorontalo District Secretary. This is in accordance with the theory used by Keith Davis which states some factors affecting the achievement of performance such us ability, motivation and discipline. The result of interview should that the general performance of employees on the part of government secretariat district in northern Gorontalo is good enough and it is seen from various aspects of employee performancenamely factor work ability, work motivation and labor disciplin. Keyword: Performance, work ability, work motivation.